“Don Nobody”, Author of the Work of Eduardo Scala. Stages and Mystical Sources of the Scalian Poetic of Disappearance (Castilla. Estudios de Literatura, 2020)
AbstractIn the present paper, a unique case in the recent Spanish poetry is analysed: the poetics of disappearance of Eduardo Scala. Against the author’s rise in the Literary Field, Scala carries out a self-annihilation process in two phases. First, he burns all his previous work and renames himself as “Don Nobody” to achieve a mystical de-identification endeavour. Thanks to this closure, it is possible the next stage: a “new birth” that causes the opening of the poetry.Scala’s production begins in the Spanish Literary Postmodernity. He has valued the negative artistic proposals of Marcel Duchamp or John Cage and he knows the philosophy of Roland Barthes and his text The Dead of Author. However, the main sources of Scala are found in the mystical tradition; specially, two concepts are essential: “resignation” and “nothingness”. To complete the explanation of this ascesthetic, a sociological approach to literature will be used.
Keywords: Eduardo Scala; negativity; mysticism; ascesthetic; sociology of literature